A lack of response of the financial behaviors of biodiversity conservation nonprofits to changing economic conditions. Issue 23 (3rd November 2014) - Larson, Eric R.; Boyer, Alison G.; Armsworth, Paul R.
Abstract The effectiveness of conservation organizations is determined in part by how they adapt to changing conditions. Over the previous decade, economic conditions in the United States (US) showed marked variation including a period of rapid growth followed by a major recession. We examine how biodiversity conservation nonprofits in the US responded to these changes through their financial behaviors, focusing on a sample of 90 biodiversity conservation nonprofits and the largest individual organization (The Nature Conservancy; TNC). For the 90 sampled organizations, an analysis of financial ratios derived from tax return data revealed little response to economic conditions. Similarly, more detailed examination of conservation expenditures and land acquisition practices of TNC revealed only one significant relationship with economic conditions: TNC accepted a greater proportion of conservation easements as donated in more difficult economic conditions. Our results suggest that the financial behaviors of US biodiversity conservation nonprofits are unresponsive to economic conditions.